Application of the indonesian financial Accounting standards no 109 at zakat Management organization period 2012 to 2016 - Muammar Aditya (Jurnal Manajemen Dakwah, 2018)
The objective of PSAK No. 109 is regulating the recognition, measurement, presentation and disclosure of zakat and infaq/sadaqah transaction and scope of standard are applied to Amil, which collect or receive and distribute zakat and infaq/sadaqah. Contain of PSAK No 109, mainly divide into 4 parts are recognition and measurement, presentation, and disclosure of zakat and infaq/sadaqah transaction. This study aims to see how application of financial statements of Baznas, Dompet Dhuafa, PKPU and Rumah Zakat from their website form 2012–2016 based on PSAK No. 109. The analytical method used is descriptive qualitative. Result and conclusion of this study are Baznas is the highest average percentage and PKPU is the lowest from presentation of Statement of Financial Position, Statement of Fund Changes, Statement of Assets Changes Under Management, Statement of Cash Flows, and Notes to the Financial Statement.